(untitled) (Medicine Today, 2015)
Ambulatory ECG monitoring is suitable for patients with symptoms which may be caused by arrhythmia such as palpitation, light-headedness, syncope or chest discomfort. Patients with symptoms occurring daily or almost daily or those who have syncope without warning may be evaluated with a 24 hour Holter monitoring. Objective of this study is to determine incidences of various arrhythmias on 24-hour electrocardiographic Holter monitoring. This retrospective cross-sectional descriptive study was carried out in the cardiology department of NICVD by reviewing the Holter monitoring report to study different types of cardiac arrhythmias. Adult patients of either gender, referred for Holter monitoring with symptoms of palpitation, dizziness and syncope were evaluated for arrhythmia. The data analysis of the 100 patients who were studied, showed that there were 75 (75%) males and 25 (25%) females. 25% of patients were below 40 years whereas 75% were above 40 years of age. 67(67%) patients developed arrhythmia and others were normal. 38% report showed ventricular ectopic, 11% sick sinus syndrome, 5% ventricular tachycardia, 3% complete heart block. Supraventricular ectopic, atrial flutter, atrial fibrillation and Wolf Parkinson White syndrome each developed in only 1% of patients. Twenty four hour Holter monitoring is an important investigation for evaluation of patients with palpitation, dizziness and syncope. Arrhythmias were detected frequently in both symptomatic and asymptomatic patients. One must be careful to avoid attributing a symptom to an arrhythmia until a close temporal relationship is demonstrated. Medicine Today 2014 Vol.26(2): 71-74